Free school bus service for needy children in Surabaya : Finding the optimal route using geographic information system / Daniel Hary Prasetyo - Prasetyo, Daniel Hary (2012)
Surabaya city, Indonesia, has a considerable number of unschooled children. Even though the Government has eliminated the tuition fee, the number of needy school aged children remains high because of additional schooling costs beyond the tuition fee. The Government tries to support the needy student population by donating money for books, uniforms, shoes, and other school supplies, and would also like to offer help by easing transportation costs. The distribution of upper school make the traveling length and traveling costs excessive, compared with lower level schools. This goal of this research is to provide a clear framework of methodology and analysis which will serve to assist the government in analyzing the probability of the use of school buses in supporting the needy with their transportation. The work begins with an exploration of the research area and the related technology. This research is in the vehicle routing problem area, with a special emphasis on the school bus. The environment is an urban area, with uniform fleet, across multiple schools. Within this concept, that data that will be required is defined. This research requires a needy area map, street map, school map, depot map, and existing transportation map. The concept then details in a methodology. From the methodology it is noted that there are several types of work which must be completed over 3 broad stages: preprocessing, routing and analyzing. In the preprocessing stage, the needy area must be refined, the network dataset needs to be built, and the visiting places and the number of passengers in the street segments need to be generated. In the routing stage, some experimentation is required and is useful with respect to looking at the street network in different settings, discovering how many routes need to be provided to cover all needy areas and school locations. There are two analyst processes in the analyzing stage; load analyst and accessibility analyst. The load analyst will show the passenger flow characteristic and the accessibility analyst will show the effect of the school buses in the existing transportation system. Several models have been developed for different functionalities. The routing model is used repetitively and each output is assessed and compared. This assessment is based on load balancing, number of covered needy, time consumed, and shared area. The best route is then discovered and analyzed. Finally, the route is evaluated with ground checking. The positive results of the research and its methodology are twofold: the methodology provides a framework for analysis that can be easily and effectively used by government to make decisions regarding the creation of practical and acceptable bus routes to help needy families. Secondly, the methodology also provides a useful new starting point in those cities across the world that lack sufficient spatial data in conducting VRP research.